Sistema de talleres de educación sexual para la prevención de relaciones sexuales precoces en adolescentes - Macas Ajila, Yessenia Marisol (Machala, Universidad Técnica de Machala, 2023)
The study was aimed at developing a "Sex education workshop system for the prevention of early sexual relations" in the tenth year students of Basic General Education at the Eva Batallas de Falquez School. As an investigative problem, the following was raised: How to prevent early sexual relations in adolescents of the Tenth Year of the School of Basic General Education "Eva Esperanza Batallas de Falquez"?, as a research object, early sexual relations in tenth-year students were studied anus. The general objective of the study was to develop a system of sexual education workshops that contributes to the prevention of early sexual relations in adolescents through recreational play days, values and reflective workshops. A survey was applied to 60 students and an interview to 5 teachers and 4 directors of the aforementioned school. The main results showed that approximately 63.33% of male and female students have early sexual relations. It was determined that at the level of the parents they do not have talks with their children about sexuality issues, as well as that 31.6% of the students have not received any kind of talks on sexual education in the educational unit. The teachers who teach classes at this level of study also expressed that they are not trained to be able to offer sexual education topics during the development of their classes. These results allowed us to establish the proposal, which had its feasibility and application validated through expert judgment, which determined a truth value equal to 0.95 for Aiken's V.
El estudio, se direccionó a elaborar un “Sistema de talleres de educación sexual para la prevención de relaciones sexuales precoces” en los estudiantes de décimo año de Educación General Básica en la Escuela Eva Batallas de Falquez. Como problema investigativo se planteó: ¿Cómo prevenir las relaciones sexuales precoces en los adolescentes de Decimo Año de la Escuela de Educación General Básica "Eva Esperanza Batallas de Falquez"?, como objeto investigativo se estudió las relaciones sexuales precoces en los estudiantes de décimo año. El objetivo general del estudio fue: elaborar un sistema de talleres de educación sexual que contribuya a la prevención de las relaciones sexuales precoces en los adolescentes mediante jornadas lúdicas recreativas, valores y talleres reflexivos. Se aplicó una encuesta a 60 estudiantes y una entrevista a 5 docentes y 4 directivos de la escuela antes mencionada. Los principales resultados demostraron que aproximadamente el 63,33% de los estudiantes, entre hombres y mujeres, tienen relaciones sexuales precoces. Se determinó que los padres de familia no mantienen conversaciones con sus hijos sobre temas de sexualidad, así como también que el 31,6 % de los estudiantes no han recibido algún tipo de charla de educación sexual en la unidad educativa. Los docentes que imparten clases en este nivel de estudio también expresaron que no están capacitados para poder brindar temas de educación sexual durante el desarrollo de sus clases. Estos resultados permitieron establecer la propuesta, la cual tuvo una validación de su factibilidad y aplicación a través de un juicio de expertos, los cuales determinaron un valor de verdad igual a 0.95 para la V de Aiken.
Keywords: Anticonceptivos; educación; prevención; sexualidad; talleres